2017
DOI: 10.1016/j.jcmgh.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Mend Your Fences

Abstract: The intestinal epithelium can be easily disrupted during gut inflammation as seen in inflammatory bowel disease (IBD), such as ulcerative colitis or Crohn’s disease. For a long time, research into the pathophysiology of IBD has been focused on immune cell–mediated mechanisms. Recent evidence, however, suggests that the intestinal epithelium might play a major role in the development and perpetuation of IBD. It is now clear that IBD can be triggered by disturbances in epithelial barrier integrity via dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
222
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(227 citation statements)
references
References 168 publications
(216 reference statements)
1
222
0
4
Order By: Relevance
“…The intestinal mucosal barrier plays an essential role in protecting homeostasis against the chaotic invasion of many antigens from the external environment (Martini, Krug, Siegmund, Neurath, & Becker, 2017;Turner, 2009). Genome-wide association studies have identified several UC-susceptible genes involved in intestinal barrier function, including HNF4, CDH1, and LAMB1 (Oshima & Miwa, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal mucosal barrier plays an essential role in protecting homeostasis against the chaotic invasion of many antigens from the external environment (Martini, Krug, Siegmund, Neurath, & Becker, 2017;Turner, 2009). Genome-wide association studies have identified several UC-susceptible genes involved in intestinal barrier function, including HNF4, CDH1, and LAMB1 (Oshima & Miwa, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 A basal paracellular passage pathway is assumed to exist for larger solutes (>4 Å), 1,5 and this leak pathway is believed to be dysregulated in diseases such as inflammatory bowel disease (IBD) or celiac disease (CD), or possibly even to contribute to their induction. 3,[6][7][8] It has been a long-standing issue to get behind the cellular and molecular mechanisms of the leak pathway with occludin, as one of the tight junction proteins, being suggested to regulate it. [9][10][11][12][13][14][15] Partly on this account, occludin is considered a key marker of epithelial barrier function.…”
Section: Introductionmentioning
confidence: 99%
“…Our in vitro findings suggest the antiproliferative effects of HSGGT1 to colon epithelial cells could contribute to the deterioration of intestinal barrier integrity. Impaired barrier function is a defining characteristic of IBD, and it is hypothesised to initiate and promote unregulated and sustained proinflammatory responses by allowing excessive penetration of luminal bacteria and foreign antigens into the lamina propria (Abraham & Cho, 2009;Martini, Krug, Siegmund, Neurath, & Becker, 2017;Thoreson & Cullen, 2007;Xavier & Podolsky, 2007 In conclusion, we have shown H. saguini expresses an enzymatically active GGT homologue with potential virulence properties. Gibco/Thermo Fisher Scientific, Grand Island, NY) at 37°C with 5% CO 2 .…”
Section: Discussionmentioning
confidence: 74%